SOCIAL ENGINEERING AND SOCIAL SELF-ORGANIZATION AS MEANS OF BROADCASTING OF SOCIO-CULTURAL POTENTIAL OF GLOBAL INFORMATION NETWORKS - Ягодзінський, С. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
Information architectonics of network social engineering is analyzed, the mechanisms of its realization in postmodern culture are revealed. The article substantiates the view of the limited nature of social self-organization and impossibility of the full realization of sociocultural potential of information networks in the global context.